Pengaruh Kepercayaan dan Switching Cost terhadap Loyalitas Pengguna Jasa Kiriman Barang pada PT. Citra Van Titipan Kilat Cabang Bukittinggi - Abror, Abror; Firman, Firman; Deswita, Syilvia (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2013)
The aim of this study are to determine : (1) the effect of trust on customer loyalty of PT. Citra Van Titipan Kilat branch of Bukittinggi, and (2) the effect ot switching cost on customer loyalty of PT. Citra Van Titipan Kilat branch of Bukittinggi. This research is a causative research, which is describe about the relationship between trust, switching cost and customer loyalty of PT. Citra Van Titipan Kilat branch of Bukittinggi, the population of the study was the customer who have used the services of freight on PT. Citra Van Titipan Kilat branch of Bukittinggi, while the sample in this study was 200 (two hundred) of respondents. The sampling technique is accidental sampling. The results of study show that: (1) the trust have significant positive influence toward customer loyalty freight services on PT. Citra Van Titipan Kilat branch of Bukittinggi, and (2) switching cost significant positive influence toward customer loyalty freight services on PT. Citra Van Titipan Kilat branch of Bukittinggi.